A conceptual analysis of the potential use cases of blockchain and NFT technology for cultural heritage museum institutions to present their collections, support preservation efforts and engage visitors - a Non-Fungible Castle case study - Doehring, William; Prokůpek, Marek, 1987-; Grosman, Jakub; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This bachelor’s thesis looks at how blockchain and NFT technology can be utilized by cultural heritage museum institutions for the purpose of authentically pursuing their missions through digital initiatives in a way that overcomes the challenges associated with traditional web2 digitization projects. The subject of this thesis is the Non-Fungible Castle initiative of the Lobkowicz family. Through an analysis of this initiative, the main aim is to determine how the conceptual fundamentals of the technology present opportunities for cultural heritage museum institutions to present their collections, support preservation efforts and engage audiences. Information is gathered through interviews with members of the family, press releases, social media activity of associated individuals along with the author’s own experience of working on the Non-Fungible Castle initiative.
Vedoucí práce: Marek Prokůpek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: arts management [obor bakal. práce]; bakalářské práce; bachelor's theses